2019
DOI: 10.1002/ange.201913303
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Coupling Effect in a Photocatalytic RuII‐PdII Cage with TTF Guest as Electron Relay Mediator for Visible‐Light Hydrogen‐Evolving Promotion

Abstract: A nanocage coupling effect from a redox RuII‐PdII metal–organic cage (MOC‐16) is demonstrated for efficient photochemical H2 production by virtue of redox–guest modulation of the photo‐induced electron transfer (PET) process. Through coupling with photoredox cycle of MOC‐16, tetrathiafulvalene (TTF) guests act as electron relay mediator to improve the overall electron transfer efficiency in the host–guest system in a long‐time scale, leading to significant promotion of visible‐light driven H2 evolution. By con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 60 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…The use of encapsulated transition metal catalysts, as exemplified by Toste, Raymond, and Bergman, can be viewed as a form of biomimetic holocatalysis. While common in nature, manipulation of redox properties using synthetic hosts is much less common, even less so for catalytic applications . Herein we show that the binding of several commercially available quinones by a simple coordination cage generates catalytic activity not inherent in either component.…”
mentioning
confidence: 86%
“…The use of encapsulated transition metal catalysts, as exemplified by Toste, Raymond, and Bergman, can be viewed as a form of biomimetic holocatalysis. While common in nature, manipulation of redox properties using synthetic hosts is much less common, even less so for catalytic applications . Herein we show that the binding of several commercially available quinones by a simple coordination cage generates catalytic activity not inherent in either component.…”
mentioning
confidence: 86%
“…[12][13][14][15][16][17][18][19] This strategy takes the highly directional metal-coordination bonds to prepare SCCs spontaneously and endows the SCCs with high structural and functional diversity. [20][21][22][23][24][25][26][27][28] Especially, the preparation of photosensitizers using this method not only avoids their self-aggregation through the formation of geometric structures, but also facilitates the intersystem crossing owing to the introduction of heavy metal atoms, giving high 1 O 2 generation ability and photostability. [29][30][31][32][33][34] Moreover, different buliding blocks capable of generating 1 O 2 can be integrated into a single metallacage.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have demonstrated that dye-loaded redox-active capsules are capable of enhancing the stability of charge separation states 13 , via the fast pseudo-intramolecular electron transfer from the excited state of dyes to the metal ions, for light-driven hydrogen evolution and hydrogenation reactions using the in situ formed green H-source 14 , 15 . We envisioned that fine tuning the entry behavior of electron donors into the hosts would balance the kinetics between electron injection and substrate reduction, generating unique selectivity different from the reported abiotic manifolds 16 , One of the important catalytically relevant but still sluggish conversions is selective reduction of nitroarenes into azo products 17 20 , due to the inherent complexity of the nitro reduction processes 21 24 and the distinctive application of azo compounds in the areas of liquid crystals, photochemical switches and sensitive shuttles (Fig.…”
Section: Introductionmentioning
confidence: 99%